2009
DOI: 10.1007/s12311-009-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracerebellar MRI—Lesions in Ataxia Telangiectasia Go Along with Deficiency of the GH/IGF-1 Axis, Markedly Reduced Body Weight, High Ataxia Scores and Advanced Age

Abstract: Ataxia telangiectasia (AT) is a rare autosomal recessive disorder characterized by progressive ataxia, neurodegeneration, immunodeficiency, and cancer predisposition. Pathoanatomical studies reported a degeneration of cerebellar Purkinje cells as the striking feature of the disease. Although recent studies suggested the involvement of extracerebellar structures such as the brainstem and basal ganglia, this has rarely been studied in human AT. Thus, we performed a detailed cliniconeuroradiological investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
3
32
1
Order By: Relevance
“…In the present study, we clearly showed that the majority of patients with A-T are short in stature and many of them have altered IGF-1 and IGF-BP3 levels. This finding is not entirely new, and it has been recently reported by many authors (Arasimowicz et al, 2009;Hong & Ammann, 1970;Kieslich et al, 2010;Schubert et al, 2005;Woods & Taylor, 1992). Although the IGF-1 levels are reduced in A-T, the temporal and/or causal relationships between the lower IGF-1 levels, growth retardation and the disease process in A-T remain uncertain.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, we clearly showed that the majority of patients with A-T are short in stature and many of them have altered IGF-1 and IGF-BP3 levels. This finding is not entirely new, and it has been recently reported by many authors (Arasimowicz et al, 2009;Hong & Ammann, 1970;Kieslich et al, 2010;Schubert et al, 2005;Woods & Taylor, 1992). Although the IGF-1 levels are reduced in A-T, the temporal and/or causal relationships between the lower IGF-1 levels, growth retardation and the disease process in A-T remain uncertain.…”
Section: Discussionsupporting
confidence: 71%
“…Basal ganglia pathological conditions were not explicitly seen in our study, despite the array of A-T characteristics observed in our clinical observations (Table 3.1); however, abnormalities in this structure have been previously recorded both in post-mortem study 92 and in radiological findings, 155 particularly in older patients. As we have already mentioned, our particular A-T cohort consisted of very young patients; therefore, future work in A-T should include older A-T subjects as well as younger patients to provide an age-specific timeline of neuropathology in A-T.…”
Section: Discussioncontrasting
confidence: 62%
“…148,154 Both of these lesions were displayed with low intensity on T1-weighted images and high intensity on T2-weighted images. 148 General spinal atrophy and abnormalities in the basal ganglia have also been reported in older A-T patients, 155 supporting post-mortem spinal study findings in older A-T patients, but lacking specific anatomical detail (see 'Spinal Cord' section).…”
Section: Summary Of Radiological Findings In A-tmentioning
confidence: 70%
See 1 more Smart Citation
“…Classic A-T occurs with cerebellar and extracerebellar pathology 33,34 and imaging abnormalities, [35][36][37] with cerebellar granular and Purkinje cell loss being the most consistent feature. 35 MRI examinations in classic A-T revealed, in 1 of 2 patients with prominent movement disorders, obvious basal ganglia pathology 37 ; 1 patient with prominent dystonia had a unilateral putaminal hyperintensity on T2-weighted images and bilateral decreased striatal [ 123 I]iodobenzamine binding with SPECT imaging. 24 It is unlikely that dystonia in variant A-T can be attributed solely to cerebellar atrophy, because this feature was not prominent on MRI in any of our subjects, and in another subject with variant A-T with prominent early-onset dystonia, nonspecific cerebellar atrophy without a cerebellar functional correlate was present.…”
Section: Additional Clinical Featuresmentioning
confidence: 99%